2011
DOI: 10.1002/pat.1529
|View full text |Cite
|
Sign up to set email alerts
|

The maleimide modified epoxy resins for the preparation of UV‐curable hybrid coatings

Abstract: In the present study, maleimide-modified epoxide resin containing UV-curable hybrid coating materials were prepared and coated on polycarbonate substrates in order to improve their surface properties. UV-curable, bismaleimide-modified aliphatic epoxy resin was prepared from N-(p-carboxyphenyl) maleimide (p-CPMI) and cycloaliphatic epoxy (Cyracure-6107) resin. The structure of the bismaleimide modified aliphatic epoxy resin was analyzed by FTIR and the characteristic absorption band for maleimide ring was clear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…These precursors, which have to be thermally or photo-chemically cured leads to an organic network, tangled up to the inorganic one. Close to this approach, it is also reported that the addition of pure organic monomers to the network former performs a double reticulation and creates a convolution of both O/I networks [4,10,[22][23][24][25]. In any case, sol-gel process mastery is primordial to prepare a stable sol, able to be deposited and reticulated in a three dimensions O/I hybrid network.…”
Section: Introductionmentioning
confidence: 92%
“…These precursors, which have to be thermally or photo-chemically cured leads to an organic network, tangled up to the inorganic one. Close to this approach, it is also reported that the addition of pure organic monomers to the network former performs a double reticulation and creates a convolution of both O/I networks [4,10,[22][23][24][25]. In any case, sol-gel process mastery is primordial to prepare a stable sol, able to be deposited and reticulated in a three dimensions O/I hybrid network.…”
Section: Introductionmentioning
confidence: 92%
“…Moreover, considering the potential impact of residual solvent on performances of the hybrid coating materials, two sols T1K2E0 and T1K2E6 were used to form samples H-TIK2E0 and H-T1K2E6 in the same operation, respectively. According to relevant literatures [25,38], their UVcuring properties were studied by FTIR spectroscopy, which is based on recording the change in (C=C) double bond absorption of acrylate groups at 1,634/cm. In one set of experiments, the formulations were coated on KBr disks in the usual way.…”
Section: (C=c) Double Bond Conversion Of Uv-curable Hybrid Coating Fomentioning
confidence: 99%
“…7, it can be found that (C=C) double bond conversions of the blank, H-T1K2E6, H-T1K2E6-A, H-TIK2E0 and H-TIK2E0-A are 88, 75, 72, 66 and 65 %, respectively. It should be mentioned that the acrylate group of MPS may have a lower activity, and is restricted by the colloidal matrix [25,38]. Based on the reason, it can be explained that, (1) (C=C) double bond conversions of the hybrid system (H-T1K2E6, H-T1K2E6-A, H-TIK2E0 and H-TIK2E0-A) are lower 13-23 % than that of the blank; (2) in the hybrid system, conversions of H-TIK2E0 and H-TIK2E0-A are lower than those of the other two because …”
Section: (C=c) Double Bond Conversion Of Uv-curable Hybrid Coating Fomentioning
confidence: 99%
“…Consequently, epoxy resins are used for a wide range of applications such as adhesives, coatings, mechanic and electronic materials, molding compounds, composites, and in structural application [4][5][6][7][8][9][10][11]. Although epoxy resins are used for a wide range of applications, their brittleness, due to the high crosslink density in epoxy cure systems, is a major drawback for several advanced applications [12][13][14].…”
Section: Introductionmentioning
confidence: 99%